AN INFRARED STUDY OF THE REMARKABLE DUSTY M-STAR HR-3126 - Chiar, J; Whittet, D; Aitken, D; Roche, P; Smith, C; Walker, H; Whitelock, P; Wright, C (Institute of Physics Publishing, 1993)
HR 3126 is a unique M giant star embedded in the bipolar reflection nebula IC 2220. Its evolutionary status is uncertain, and both the composition of the dust shell and the mechanism responsible for its ejection have proved controversial. In this paper we present new photometric and spectroscopic observations of HR 3126 and combine them with existing data from the literature in an extensive reappraisal of the star's properties at infrared wavelengths. The spectral energy distribution is consistent with an optical classification of M0-3 II with infrared excess. The dust shell cannot be fitted by a single-temperature blackbody: at least three components are required, with temperatures in the range 35-1300 K. On the basis of spectroscopy at 1-4 and 7-25 μm, combined with an assessment of various color-color diagrams, we are able to reject the hypothesis that HR 3126 is carbon-rich. Weak silicate emission features are detected at 10 and 19 μm, and a previous report of silicon carbide emission at 11.2 μm is not substantiated. Our results are discussed with a view to discrimination between proposed scenarios for the evolutionary status of the star. Although it is not yet possible to draw definitive conclusions, it seems likely that HR 2136 is in a phase of advanced and rapid post-main-sequence evolution, possibly beginning its ascent of the asymptotic giant branch.